Стратегія реформи економічного збагачення - Ковальов, Євген Володимирович (НТУ "ХПІ", 2016)
Оглянутий хід реформування соціально-економічного розвитку України. Встановлений незадовільний стан проведення реформ. Уряд поставив амбітні цілі вдосконалення країни. Але серед пріоритетних напрямків і програм відсутня реформа економічного розвитку. Тому в статті в якості головної запропонована стратегія економічного збагачення. Пропонується визначити провідну роль вітчизняних корпорацій в збільшенні експортних надходжень і інноваційному розвитку країни. Встановлено стратегічні напрямки, фактори, елементи організаційного забезпечення реформи.

It is established that as a result of military operations, the loss of large areas, reduced economic potential, Ukraine is currently in a very difficult economic situation. Relevant is the reform of the social – economic situation of the country. The government has set ambitious targets countries. President of the Sustainable Development Strategy approved "Ukraine-2020". But among the priorities of reforms and programs is not the main – reform of economic enrichment of the country. Despite the loss, our country still has a large industrial, agricultural, resource and intellectual potential. Real Ukraine enrichment possible mainly due to external markets: European, US and Chinese markets. The decisive role in the development of export earnings and the markets of developed countries belongs to large enterprises in the organizational form of international corporations. It is proposed to define a leading role in the development of export earnings and the markets of developed countries large enterprises in the organizational form of international corporations. For a real building a solid technological base of production of high quality goods purchased for licenses and quickly learns modern Western technology.
Economic reform strategy of enrichment
Keywords: економіка; реформування; розвиток інноваційний; розвиток сталий; стратегія; безпека економічна; економіка "сировинна"; economic reform; innovative development; sustainable development; strategy; economic security; "raw" economy